Factors Affecting Employee Job Satisfaction in Nepalese Hospitality Industry: A Study of Hotels in Bhaktapur - Hakuduwal, Kishor (Nepalese Journal of Hospitality and Tourism Management, 2021)
The objective of the study is to analyse the factors affecting employee job satisfaction in hotels of Bhaktapur, Nepal. Compensation and reward, working environment, career development, job security and co-workers are taken as independent variables and employee job satisfaction as a dependent variable. Using the purposive sampling, 153 employees were selected, and a questionnaire survey was carried out to collect data. Using regression analysis, the study found that compensation and reward, working environment, career development, and job security have significant impact on employee job satisfaction but the relationship with co-workers has negative significant impact on employee job satisfaction in hotels of Bhaktapur. Likewise, the study also revealed that job security has the highest positive significance on employee job satisfaction in hotels of Bhaktapur followed by compensation and reward, working environment and career development opportunities.